Understanding the rapid shrinkage of glaciers in the Karatal river basin (Journal of Geography and Environmental Management, 2016)
Glaciers are among the world's best recorders of, and first responders to, natural and anthropogenic climate change and provide a time perspective for current climatic and environmental variations. According to our previous results, glaciers in the Karatal river basin shrinking faster than other glacierized catchments of Central Asian mountains, including Tien-Shan, Altai and Pamir. In our investigation, we consider and discuss the possible factors of dramatically decreasing glaciers in the Karatal river basin, and their role in glacier fluctuation. We conclude that considered glacierized basin are located in the most unfavorable conditions for glaciation, and as a result showed a higher shrinkage rate than other glacierized regions of the Central Asia from 1956 to 2012.
Keywords: glacier shrinkage; Karatal river basin; topographic factors; climate change.